2019
DOI: 10.3390/ma12193165
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Static Load in the UNSM Process on the Corrosion Properties of Alloy 600

Abstract: To suppress stress corrosion-cracking, compressive residual stresses, such as shot peening, laser peening, water jet peening, ultrasonic peening, and ultrasonic nanocrystal surface modification (UNSM) are utilized. However, among the numerous techniques, there is little research about the corrosion effect of detailed conditions, such as static load or amplitude in UNSM. A study on UNSM among various techniques of adding compressive residual stress to Alloy 600 was conducted. The focus of this study was on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…An excessive load increases the friction between the ball tip and material. It appears that such an increase in friction causes excessive plastic deformation [30] and decreases the roughness improvement rate. On the other hand, with low loads applied to D2-H55, as shown in Fig.…”
Section: Surface Topographymentioning
confidence: 99%
See 2 more Smart Citations
“…An excessive load increases the friction between the ball tip and material. It appears that such an increase in friction causes excessive plastic deformation [30] and decreases the roughness improvement rate. On the other hand, with low loads applied to D2-H55, as shown in Fig.…”
Section: Surface Topographymentioning
confidence: 99%
“…It is estimated that the roughness improvement rate is reduced when a load of 50 N is applied to D2-H40 owing to the generation of these wave patterns and cracks. In addition, these features may act as starting points for corrosion, thereby reducing the corrosion resistance [30]. In the case of D2-H55, however, the top surface was leveled through the ball tip, unlike D2-H40, as shown in Fig.…”
Section: Surface Topographymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hou et al 26) utilized UNSM technology to process AZ31B Mg alloy, the results showed that UNSM could significantly improve the mechanical properties of Mg alloys without compromising their corrosion rate. Kim et al 27) focus on the effect of the static load in UNSM on the corrosion properties of Alloy 600, they found that an increase in static load under critical static load improved corrosion performance.…”
Section: Introductionmentioning
confidence: 99%
“…Heterostructured materials are a new class of materials with artificial microstructural heterogeneities, and their unique strengthening mechanisms effectively contribute to strength-ductility synergy. Accordingly, microstructural approaches using SPD have been shifted to tailoring the heterogeneous microstructure by partial grain refinement, such as plastic flow machining [11] and ultrasonic nanocrystalline surface modification [12,13].…”
Section: Introductionmentioning
confidence: 99%